The aftermath of COVID‐19 in dermatology practice: What's next? - Ng, Janice Natasha (J Cosmet Dermatol, 2020)
The rapidly increasing number of COVID‐19‐infected patients and evidence of human‐to‐human transmission even within the asymptomatic incubation period prompted the attention of the entire world. The field of dermatology and procedural dermatology is not exempt from this global issue. We cannot deny the fact that this situation will have a lasting impact on the health‐seeking behaviors of our patients. It is necessary for dermatologists and dermatologic surgeons to be aware of the potential risks and precautions when re‐emerging their practices after COVID‐19.